Writing an expository text using augmented reality: Students' performance and perceptions - Koc, Ozge; Altun, Emin; Yuksel, H. Gulru (SPRINGER, 2022)
Writing is a demanding task for learners in English as a foreign language (EFL) contexts. Students are not given sufficient practice opportunities in the classroom. Hence, they do not feel motivated to write or enjoy writing in English much, and they encounter difficulties in planning, organizing ideas, stating a clear purpose and choosing appropriate words to express their ideas while composing texts in English. Integrating advanced technologies into instruction can mitigate such problems. The main purpose of this study is to explore whether the use of AR-based materials could contribute to high school students in the process of producing texts in English. The study also seeks to explore students' perceptions on the use of AR. The study is quasi-experimental in design. The experiment was conducted in two classes of high school students with a B1 level of English proficiency. In total 48 students participated in the study. Following the design of the AR-based materials, the classes were assigned as the experimental (N = 24) and control (N = 24) group. Both groups worked on the same topic at the same time interval. Upon completion of their compositions, the students' perceptions of the use of AR-based materials were collected via a questionnaire. The statistical analyzes yielded significant differences in the writing scores between the groups. The findings indicated that the use of AR-based materials had a medium effect on the selected writing skills of the students. The results also showed that the students' perceptions of the AR-based writing experience were positive. The findings suggest that AR-based writing activities increase students' motivation towards writing, which may result in better performance.
Keywords: Augmented-reality; English as a foreign language; Student perceptions; Writing skills; ENGLISH; INSTRUCTION; TECHNOLOGY; VOCABULARY; EDUCATION; IMPACT; Education & Educational Research